An Experimental Investigation on the Effect of Aspect Ratio on the Flow-Induced Motion and Energy Harvesting of a Circular Cylinder with T-Shaped Attachments - Danjie Ran; Yizhuo Wu; Bomeng Feng; Kainan Chen; Xiang Yan; Wene Wang; Jijian Lian; Shishen Li (Journal of Marine Science and Engineering, 2026)
Water channel experiments were conducted to investigate the influence of aspect ratio (H/D = 0.9–1.9) on the flow-induced motion (FIM) and hydrokinetic energy conversion performance of an elastically mounted circular cylinder with T-shaped attachments (Cir-T-Att). The results indicate that the aspect ratio critically governs the vortex-induced vibration (VIV) to galloping transition by modulating the effective angle of attack. While larger H/D promotes galloping and higher amplitudes under low damping, this benefit is negated under elevated system damping, where amplitudes are uniformly suppressed. Consequently, the maximum power output exhibits a non-monotonic dependence with H/D. Within the investigated parametric range, peak performance occurs at H/D = 1.1, with a total damping ratio ζtotal = 0.122 and reduced velocity Ur = 11.25. For practical harvester design, the optimal H/D should be selected by aligning the intended oscillation regime with local flow characteristics.